İşletmelerde iç kontrol sisteminin incelenmesi ve muhasebe denetimindeki yeri - Zorluoğlu, Ömer Faruk (My University, 2003)
İŞLETMELERDE İÇ KONTROL SİSTEMİNİN İNCELENMESİ VE MUHASEBE DENETİMİNDEKİ YERİ Bu çalışmada etkin bir iç kontrol sisteminin nasıl olması gerektiği ve bağımsız dış denetçinin denetimi planlama aşamasında iç kontrol sistemini inceleyerek denetim çalışmasına nasıl yön verdiği üzerinde durulmuştur. Son yıllarda ekonominin gelişimi, işletmelerin büyük boyutlara ulaşmasına, iş ve işlemlerinin karmaşıklaşmasına neden olmuştur.İşletme yönetimi ve işletme ile çıkar ilişkisi bulunan kişilerin (işletme ilgilileri) işletme ile ilgili kararlar alabilmesi için doğru ve güvenilir bilgiye ulaşmaları gerekir.Bu bilgileri sağlamak işletme yönetiminin sorumluluğundadır. Günümüzde işletme yönetimleri muhasebe bilgilerinin doğru ve güvenilir olması ve ayrıca işletme varlıklarını korumak, işletme faaliyetlerinin yönetim politikalarına, planlara ve yasalara uygunluğunu sağlamak, kaynakların ekonomik ve verimli kullanımını sağlamak, faaliyetlerin belirlenmiş amaçlara ve hedeflere ulaşmasını sağlamak amacıyla işletmelerde iç kontrol sistemleri kurarlar.İç kontrol sisteminin işlerliliğini de kendi elemanları vasıtasıyla denetlerler.

EXAMINATION OF INTERNAL CONTROL SYSTEM AT BUSINESS OPERATIONS AND ITS PLACE IN ACCOUNTING AUDIT In this study it is emphasized how an effective internal control system must be and how an independent external auditor examines the internal control system during planning phase and he orients the auditing study. The development of economy in recent years has caused many business operations to become big sizes and this is resulted with complexity in their works and operations.In order the persons who have self-interest relation with the business operation management and the business operation can take decisions about the business operation, they must reach to correct and reliable information.To ensure such information is under the responsibility of the business operation management. Today, the business operation managements establish internal control systems to ensure correct and reliable information and besides, to protect the business operation assets, to ensure the operation activities to be inconformity with the management policies, plans and laws, to provide the sources to be used economically and productively, and to ensure the activities to obtain some definite purposes and targets.They control the functionality of the internal control systems by means of their own staff. Though the business operation management tries to fulfill their responsibility, the ignorance, carelessness, negligence, various problems and the information to be reported with the bad intention of the managers may be misleading.For this reason, it is not sufficient for the information users to use the information solely confirmed as reliable by the business operation management.The information users must present the information to an independent expert for confirmation of their reliability before they take financial decisions. The independent external auditor examines and evaluates the internal control system to test the reliability of the accounting information.The auditor determines the structure, time and content of the test he will apply during the auditing study according to the effectiveness of the internal control system at the business operation.The auditor explains the auditing report at the last phase of the auditing study.In the auditing report, the auditor explains the content of the studies he made and gives his opinion about the financial tables.The auditor establishes a bridge between the operation place and operation information by means of the auditing report.
Keywords: Denetim; Muhasebe